The Urgency Of Changing Law Number 31 Of 1997 Concerning Military Courts - Sapto Handoyo Djarkasih Putro; Iwan Darmawan; Roby Satya Nugraha; Nazaruddin Lathif; Yustika (UNIVERSITAS PAKUAN, 2026)
The discourse on revising Law Number 31 of 1997 concerning Military Justice is gaining momentum. Various opinions have emerged, presenting compelling reasons for the law's amendment. The Law on Military Justice was enacted during the New Order regime, which was rife with the political interests of the ruling elite. Furthermore, the substance of the law is no longer in line with legal developments in society, particularly regarding the authority of military courts, which are considered too absolute. The revision of this law must emphasize the implementation of military justice based on internal military violations. Crimes classified as general crimes, including war crimes, corruption, and human rights violations, must be tried in general courts. Keywords: urgency, change, military justice, Indonesian National Armed Forces.